IMAGE BASED MERN STACK FOR SERVICE DISCOVERY USING METHOD WEB SERVICE - Kadam, Sudhir; Patil, Aparna; Mali, Yogesh; Gurav, Sachin; Patil, Sarang Maruti; More, Rajendra (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The primary technologies used to build this "E-commerce web service using MERN" are Mongodb, Nodejs, Express, and React. All consumers can browse a large selection of products, but to add a product to their shopping basket, they must first register and log in. Customers can read reviews made by other users before making a purchase. The number of items a customer adds to their shopping basket is up to them. The quantity of a product put on the cart can thereafter be modified by the customers. Finally, customers can enter their information during checkout and submit their order by paying the appropriate amount for it. The administrator can then view the customer's data, including order details, the delivery address for the order, and whether the payment has been received. Due to the inability to try on clothing while purchasing clothing online, it might be challenging for a consumer to choose a desirable outfit on the first try. The virtual try-on assignment has the potential to greatly increase the effectiveness of creating fashion catalogues and improve online user experience. This undertaking seeks to address this issue.